Efisiensi Manajemen Modal Kerja Sebelum dan Sesudah Peristiwa Stock Split pada Perusahaan yang Terdaftar di BEI - Dayana Florencia; Bonifatius Junianto Wibowo (Universitas Katolik Soegijapranata, Semarang, 2018)
This research was conducted to determine the efficiency of working capital management carried out by companies that do stock splits. The samples used in this research are 11 firms that did stock splits in 2013. Indicators of efficiency are performance index, utilization index and efficiency index. Whereas, paired t test was used to determine the difference in the efficiency of working capital management between before and after the stock split both from the Performance Index, Utilization Index, and Efficiency Index. The results of this study indicate that the company is efficient both before and after the stock split, and there is no difference in the efficiency of working capital management between before and after the stock split. It means that all companies which did stock splits are still able to manage their working capital optimally to create sales. In the future, firms should be able to increase sales more than before so that the efficiency of working capital management becomes higher. Besides, Investors should also invest their money in the company, which has high working capital management efficiency. The reason is that firms with high working capital management efficiency usually generate large profits. For further research, it is better to use a long period of years so that the differences can be known with certainty.